(untitled) (American Scholar: Journal of Interdisciplinary Research and Knowledge, 2026)
This article analyzes the modern teaching mechanisms used in the higher education system today, the advantages of the credit-module system, the impact of digital technologies on the quality of education, and the organization of independent learning of students. The article also puts forward strategic directions for the transition from traditional to innovative education and proposals for optimizing pedagogical technologies